Angiofibrolipoma of the lower lip: A rare case report - Lisa Elizabeth Jacob; Sharlene Sara Babu; Sunil Sukumaran Nair; Sujeesh Koshy (Wolters Kluwer Medknow Publications, 2018)
Lipomas are commonly occurring benign tumors consisting of mature white adipocytes surrounded by a thin fibrous capsule. It is the most common type of soft tissue mesenchymal neoplasm. Angiofibrolipoma is a rare subtype of lipoma. The most common site of angiofibrolipoma is in the back, the neck, or the shoulders. Only a few cases have been reported to occur in the oral region. This article reports a case of a 34-year-old male patient with a chief complaint of a swelling in the lower lip for the past 2 years and was diagnosed as an angiofibrolipoma. A thorough search of the literature was carried out using Pubmed, Sciencedirect, Google Scholar, and Medline until 2018 using angiofibrolipoma as a keyword. To the best of our knowledge, this is the first case reported in the literature involving the lower lip.